ELOVLs Predict Distinct Prognosis Value and Immunotherapy Efficacy In Patients With Hepatocellular Carcinoma - Zhang, Yu; Pang, Shujie; Sun, Bo; Zhang, Minbo; Jiao, Xiaoxiao; Lai, Linying; Qian, Yiting; Yang, Ning; Yang, Wenzhuo (Frontiers in Oncology, 2022)
Background: Hepatocellular carcinoma (HCC) is a primary malignancy of the liver with high prevalence worldwide and poor prognosis. It have been verified that elongation of very long chain fatty acids gene family (ELOVLs), a group of genes that responsible for elongation of saturated and polyunsaturated fatty acids, participate in the pathogenesis and development of multiplex disease including cancers. However, the functions and prognosis of ELOVLs in HCC is still indistinguishable. Methods: Firstly, we searched the mRNA expression and survival data of ELOVLs in patients with HCC via the data of TCGA. The prognosis value of ELOVLs on HCC was assessed by Kaplan-Meier plotter and Cox regression analysis. RT-qPCR, western blot and immunohistochemistry were applied to assess the specific mRNA and protein expression of ELOVLs in HCC clinical specimens of our cohort. Then, the functional enrichment of ELOVL1 especially the pathways relating to the immune were conducted utilizing the GO, KEGG and GSEA analysis. Additionally, TIMER, CIBERSOR and tumor immune dysfunction and exclusion (TIDE) were employed to evaluate the relationship between ELOVL1 and immune responses. Finally, the correlation of ELOVL1 with genome heterogeneity (MSI, TMB, MATH, HRD, purity, ploidy, LOH, Neoantigens) and mutational landscape were also evaluated basing on the date in TCGA. Results: Significant expression alteration were observed in ELOVLs family at the pan cancer level. In liver cancer, ELOVL1 and ELOVL3 were strongly associated with poor prognosis of HCC by survival analysis and differential expression analysis. Immunohistochemistry microarray, WB and RT-qPCR confirmed that ELOVL1 but not ELOVL3 played an important role in HCC. Mechanistically, functional network analysis revealed that ELOVL1 might be involved in the immune response. ELOVL1 could affect immune cell infiltration and immune checkpoint markers such as PD-1, CTLA4 in HCC. Meanwhile, high expression of ELOVL1 would be insensitive to immunotherapy. Correlation analysis of immunotherapy markers showed that ELOVL1 has been associated with MSI, TMB as well as oncogene mutations such as TP53. Conclusion: ELOVLs play distinct prognostic value in HCC. ELOVL1 could predict the poor prognosis and might be a potential indicator of immunotherapy efficacy in HCC patients.